Penetapan Alam Sebagai Subjek Hukum - Miftakhul Shodikin (Jurnal Mengkaji Indonesia, 2023)
Abstract: Legal subjects who are believed to be the holders of rights and obligations in fact, over time always experience expansion or development. After women were recognized as having legal status and corporations as non-human legal subjects, a new legal subject emerged, namely: nature. Ecuador gave the rights to nature that were embedded in the 2008 constitutional amendments, the Whanganui River in New Zealand was recognized as a legal subject with representatives of the Maori tribe, and the Ganges and Yamuna Rivers and their attributes through a decision in HC Uttarakhand India established them as legal subjects. These three legal precedents are important breakthroughs in the concept of "legal entity". Apart from that, it is also an alternative to the stalemate problem of natural destruction and environmental crisis, so that with this the determination of nature as a legal subject cannot be avoided. Purpose: Research with the aim of knowing how to determine nature as a legal subject. Where this writing should be able to contribute to the uniqueness of the science of law especially in international law moreover this research can also contribute ideas so that it can become input and/or reference for practitioners, and public officials in decision-making, environmental activists, and all human beings who care for the balance of nature. Design/Methodology/Approach: This legal research is normative legal research. The approach used is a statute approach, a case approach, and a comparative approach. Findings: Based on historical facts, the subject of law has always been and will continue to experience expansion. After women and corporations were recognized as legal subjects several decades ago, it is now nature's turn to gain recognition as an entity holding rights and obligations. This is due to a paradigm shift in the relationship between humans and nature. The view of humans as the center of nature "anthropocentrism" is replaced with a view of deep ecology represented by ecocentrism and biocentrism environmental ethics. In essence, this view leads to the recognition of equality for every living thing or ecological justice. Originality/Value: There is no research that discusses nature as a legal subject, so this is new research.